Role and perceptions about communication: the case of new product development in the animal health industry - Tjernagel, Adam (Kansas State University, 2017)
The development of vaccines and similar pharmaceutical products in the animal health industry are expensive and follow very specific pathways to comply with regulatory requirements for product licensure and registration. The vaccine development process is complex and involves numerous individuals, assets and departments within and outside the organization, and is a long process. The study stage of this long and complex process allows a company to confirm particular solutions to particular health incidents can be efficacious. The study stage involves executives who decide on new products that may be developed, managers who oversee the development of the products and scientists who develop protocols to undertake animal studies to test various aspects of the new product. It also involves clinical study personnel and laboratory personnel who conduct the experiments and collect data for analyses about the new products being studied. The number of people and time sensitivity of the processes contribute to the complexity, making effective communication critical to getting new products developed on time and on budget. The objective of this research is to identify perceived gaps in communication among people in the different roles with the view to finding solutions to address these gaps. Data were collected using an industry-focused online survey instrument. The instrument was designed to have both closed and open-ended questions. Survey participants were purposefully selected from across the global animal health industry, focusing on those directly involved in the study stage of new product development. The results showed the majority of respondents were satisfied with their company’s processes and systems for study development, initiation and execution, but people resources were viewed as the highest contributor to bottlenecks, which could demonstrate gaps in the communication links between groups. However, perceptions about challenges and gaps in communication seem to be influenced by who is providing information and who is receiving it. The different roles perceived the effect of timeliness, accuracy and clarity of communication on product development costs differently, with scientists presenting the highest cost of communication challenges and executives the lowest. On average, the perception was that these communication challenges increased the cost at the study stage of new product development by about 84% for biologicals and over 100% for pharmaceuticals.
Keywords: Vaccine; Product development; Animal health; Communication